A Climate-Change Policy Induced Shift from Innovations in Energy Production to Energy Savings - Reyer Gerlagh (Fondazione Eni Enrico Mattei (FEEM), 2004)
We develop an endogenous growth model with capital, labor and energy as production factors and three productivity variables that measure accumulated innovations for energy production, energy savings, and neutral growth. All markets are complete and perfect, except for research, for which we assume that the marginal social value exceeds marginal costs by factor four. The model constants are calibrated so that the model reproduces the relevant trends over the 1970-2000 period. The model contains a simple climate module, and is used to assess the impact of Induced Technological Change (ITC) for a policy that aims at a maximum level of atmospheric CO2 concentration (450 ppmv). ITC is shown to reduce the required carbon tax by about a factor 2, and to reduce costs of such a policy by about factor 10. Numerical simulations show that knowledge accumulation shifts from energy production to energy saving technology.
Keywords: H23; O31; O41; Q42; Q43; 330; Induced technological change; Environmental taxes; Partial equilibrium; Klimaschutz; Endogenes Wachstumsmodell; Technischer Fortschritt; Ökosteuer; Energieeinsparung; Partielles Gleichgewicht; Simulation